Pengaruh Tingkat Pendidikan, Faktor Usia dan Gender Terhadap Literasi Keuangan Pelaku UMKM di Kota Medan - Zalukhu, Rika Surianto; Hutauruk, Rapat Piter Sony; Collyn, Daniel; Jayanti S., Suci Etri; Sinaga, Murbanto; Damanik, Sri Winda Hardiyanti (Sekolah Tinggi Ilmu Ekonomi Bina Karya, 2024)
The financial literacy index of the Indonesian population has increased, but on the other hand, the number of cases of illegal online loan scams and online trading fraud due to low financial literacy remains very high. Therefore, efforts are needed to improve the financial literacy of MSMEs based on a deep understanding of the factors influencing financial literacy itself. This study aims to determine the effect of education level, age, and gender on the financial literacy of MSME actors, both partially and simultaneously. The research was conducted on MSME actors in Medan City. The research sample consisted of 100 people. The sampling technique used was simple random sampling. This study used primary data sources. Data were obtained through questionnaires distributed to respondents. The research data were then analyzed using multiple linear regression analysis methods. The analysis results show that the education level has a positive and significant effect on the financial literacy of MSME actors in Medan City. Age has a negative and significant effect on the financial literacy of MSME actors in Medan City. Gender also has a negative and significant effect on the financial literacy of MSME actors in Medan City. Furthermore, education level, age, and gender simultaneously have a significant effect on the financial literacy of MSME actors in Medan City. The direct implication of this study is the need for the development of holistic and inclusive financial education and training programs for MSME actors.